Aplicação de resíduos de construção e demolição em estruturas de pavimento - Cintra, Pedro Guerra [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The objective of this work was collect information of articles published previously and carry out a study about them, including contents and interesting stuff that bring growth regarding the construction residues utilization and demolition (RCD), that today provides many environmental impacts. The need of utilization of the RCD in Brazil and in the world earned bigger attention world speaking, therefore the industry of the civil construction is had as one of the biggest present residues output springs. For it present a point that can be applied the RCD, is discussed in that work the kinds and structures of floors, where are presented the layers and, finally, a short argument about the possible and economic feasabilities job of the residues recycled in some layers of the structure of floor

O objetivo deste trabalho foi coletar informações de artigos publicados anteriormente e realizar um estudo sobre eles, abrangendo conteúdos e materiais interessantes que trazem crescimento em relação ao aproveitamento de resíduos de construção e demolição (RCD), que hoje proporciona muitos impactos ambientais. A necessidade de aproveitamento do RCD no Brasil e no mundo ganhou maior atenção mundialmente falando, pois a indústria da construção civil é tida como uma das maiores fontes de produção de resíduos atuais. Para apresentar um ponto que pode ser aplicado o RCD, é discutido nesse trabalho os tipos e estruturas de pavimentos, onde são apresentadas as camadas e, por fim, uma breve discussão sobre as viabilidades econômicas e possível emprego dos resíduos reciclados em algumas camadas da estrutura de pavimento
Keywords: Resíduos; Impacto ambiental